Ultrasonic sensor humidifier: KALOUD / M.Danial Haikal Masri - Masri, M.Danial Haikal (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
By 2020, the world has been rocked by the most dangerous infectious disease that can cause death. This disease or virus is called coronavirus or Covid-19 which can cause everyone to become weak and lethargic and can cause death. Malaysian government began declaring that covid in Malaysia is endemic as the number of cases is declining, and the people have been vaccinated. At this covid post, we must take precautions to ensure that the virus continues to die and will never live again. Therefore, we as students are required to create products that will ensure health and hygiene. Ka loud is one of the products taken from the humidifier to be used as a product that can maintain health and hygiene to the public to avoid covid-19. The previous use of the humidifier was for one use only and did not have more than that but this product is widely used by people because it has interesting parts to be used as decoration and sanitize. This product is helpful in terms of health and hygiene. This product is placed in the fitting room of each outlet to ensure that it can avoid the problem that often occurs that the public often enters the fitting room beyond the limit. It is also to ensure that each fitting room can be kept clean. Therefore, this humidifier is a product that will probably give a nice side effect to ensure that the covid-19 virus will not spread quickly. Obviously, this product will be able to help us to ensure the health and cleanliness of a fitting room can be maintained and all the diseases are not infected easily and quickly. Therefore, it is also designed with fun features without compromising the features of the fitting room. It also has a clothes hanger to ensure that the fitting room feature remains in use.